1994
DOI: 10.1002/mrd.1080370408
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of germ cells from fetal bovine ovaries

Abstract: Gonadal cell suspensions were made from bovine fetuses of 35-55-, 56-80-, and 80-130-day age groups corresponding to the periods predominated by primordial germ cells (PGCs), oogonia, and meiotic cells, respectively. Germ cells identified on morphological criteria prior to their isolation from suspensions were compared histochemically and morphologically with cells in cryosections, impression smears, and semithin sections of similar gonads. Oocytes were distinguished by their chromosomal configurations in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…Such cells are known to be pluripotent at least in the mouse. Gonial cells are diploid and can be isolated in large numbers from bovine foetal gonads [28]. The pluripotency of bovine gonial cells has been tested through nuclear transfer by three separate laboratories, leading to the temporary conclusion that germ cells can direct in vitro development up to blastocysts in some cases (2-4 %), but no live offspring could be obtained after transfer to recipient heifers.…”
Section: Attempts With Gonial Cellsmentioning
confidence: 99%
“…Such cells are known to be pluripotent at least in the mouse. Gonial cells are diploid and can be isolated in large numbers from bovine foetal gonads [28]. The pluripotency of bovine gonial cells has been tested through nuclear transfer by three separate laboratories, leading to the temporary conclusion that germ cells can direct in vitro development up to blastocysts in some cases (2-4 %), but no live offspring could be obtained after transfer to recipient heifers.…”
Section: Attempts With Gonial Cellsmentioning
confidence: 99%
“…Pig [17], cattle [7,18], rabbit [7,19], and rat [7,20] PGCs have been collected and characterized by their morphology and immunohistochemistry. We and others have previously shown that porcine EG cell lines can be isolated [21][22][23], genetically transformed [21], and contribute to chimera development in the pig [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In H/E-stained sections, cells possessing lightly stained round nuclei along with a maintenance of cytoplasmic volume and easily discernible spherical plasma membranes were considered nonapoptotic, whereas cells showing nuclear condensation (basophilia), cytoplasmic shrinkage, and convoluted plasma membranes were considered apoptotic (21). As previously established for studies of the fetal ovary (22)(23)(24), germ cells were distinguished from somatic cells based on differences in cellular size (germ cells being much larger than somatic cells) and morphology (germ cells and their nuclei being spherical as opposed to somatic cells being squamous with flattened nuclei). Furthermore, morphological identification of germ cells was confirmed by alkaline phosphatase staining in preliminary unpublished studies conducted during the validation of this culture model (17).…”
Section: Histologymentioning
confidence: 99%